Endodontic management of maxillary second molar with vertucci Type VI root canal morphology diagnosed using cone-beam computed tomography - Kothandaraman Sathyanarayanan; Lingeswaran Poornima (Wolters Kluwer Medknow Publications, 2018)
The objective of this article is to highlight the importance of having a thorough knowledge about the root canal anatomy and the possible anatomical variations in maxillary second molar. This case report presents the endodontic management of the left maxillary second molar with four roots and four canals. A cone-beam computed tomography (CBCT) imaging was performed to ascertain this complex root canal anatomy. The CBCT findings revealed that the distobuccal canal and the distopalatal canal of the left maxillary second molar exhibits Vertucci Type VI root canal anatomy. This case report demonstrates the usefulness of CBCT in the understanding of complex root canal anatomy of maxillary second molar and its potential use as an endodontic diagnostic tool.